1975
DOI: 10.1021/jf60199a008
|View full text |Cite
|
Sign up to set email alerts
|

Heats of adsorption of small molecules on lactose

Abstract: This study has demonstrated that a wide variety of organic compounds, including esters, aldehydes, ketones, alcohols, and hydrocarbons, adsorb on stable, anhydrous «-lactose. The heats of adsorption of these compounds on stable, anhydrous a-lactose have been determined by the gas chromatographic method, and are taken as indications of the strengths of adsorption. On this basis it has been established that for a given

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 7 publications
4
15
0
Order By: Relevance
“…This value also agrees with Aspelund's value of 6.48. The resulting difference in AH between heptane and heptanone and heptanone and heptanol is then 5-6 kcallmole (McMullin et al 1975), which makes it reasonable to assume that adsorption involves nonspecific interaction plus one hydrogen bond for carb onyls or two hydrogen bonds for alcohols, This conclusion necessitates that the adsorbent (soy protein) have numerous polar binding sites that would facilitate formation of two hydrogen bonds.…”
Section: Heats Of Adsorptionmentioning
confidence: 99%
“…This value also agrees with Aspelund's value of 6.48. The resulting difference in AH between heptane and heptanone and heptanone and heptanol is then 5-6 kcallmole (McMullin et al 1975), which makes it reasonable to assume that adsorption involves nonspecific interaction plus one hydrogen bond for carb onyls or two hydrogen bonds for alcohols, This conclusion necessitates that the adsorbent (soy protein) have numerous polar binding sites that would facilitate formation of two hydrogen bonds.…”
Section: Heats Of Adsorptionmentioning
confidence: 99%
“…Simplicity, speed, and accuracy (in most cases) are the advantages of using the chromatographic technique over other techniques for the determination of thermodynamic functions (Gale and Beebe, 1964). McMullin et al (1975) used this method with lactose, and Aspelund and Wilson (1979) demonstrated that the method could also be used with soy protein. More recently Ehler et al (1979) and Crowther et al (1981) have used the method with lactose, sucrose, glucose, and processed soy isolate.…”
mentioning
confidence: 99%
“…One of the first studies on this subject was realized by McMullin et al (1975), which demonstrated that lactose has a great ability to adsorb aromas. The heats of adsorption of a large variety of organic compounds (esters, aldehydes, ketones, alcohols and hydrocarbons) on anhydrous lactose were compared (Table 11).…”
Section: Igc To Investigate Interactions Between Flavor Compounds Andmentioning
confidence: 99%
“…-DH (kcal/mol) Soy protein isolate Lactose Aspelund and Wilson (1983) Crowther et al (1981) Zhou and Cadwallader (2006) McMullin et al (1975 n-Hexane Volatile polar probes such as 1-hexanol and hexanal have higher binding affinities than an apolar one (hexane) due to hydrogen binding interactions with SPI. The retention of these polar probes are weaker at 30% RH, indicating possible competition for binding sites on the SPI surface between these volatile probes and water molecules.…”
Section: Flavormentioning
confidence: 99%